Samuel Johnson in Historical Context - Clark, J. author. aut Link
XII, 318 p.
Keywords: In one of the more sudden shifts of perspective, and hotly contested controversies of recent historical and literary scholarship, our view of Johnson has been fundamentally changed. This volume offers the best up-to-the-moment account of what has been achieved, and points to the new directions in which scholarship is developing. It will be essential reading for all concerned with eighteenth-century studies.